Evaluation of Ageism Attitudes Of Clinical Physical Therapists : Ageism Attitudes of Clinical Physical Therapists - Noor, Kamishwa; Khalid, Tahreen; Jabbar, Saima; Khalid Khan, Abdullah; Azam, Hafsa; Anwar, Arslan; Khalid Khan, Umar (Pakistan Journal of Health Sciences, 2022)
Considering rising number of older people worldwide, provision of quality healthcare services has become matter of concern. Since, healthcare practitioners’ attitudes towards ageism affect quality of the care provided to the older population. Objective: To evaluate the ageism attitude of clinical physical therapists towards older people. Methods: A cross sectional study was conducted at various public and private sector clinical settings in Faisalabad. 118 participants who were clinical physical therapists with at least one-year clinical experience, currently practicing and willing to participate were included. Geriatrics attitude scale and facts on aging scale were used as outcome measures. SPSS (V.24) was used for analyzing the data and results were interpreted using frequency tables and chi square. Results: The 83.1% participants belonging to age group 24-30 years while 79.7% were female physical therapists.80.5% had been working for more than one year. Attitude was measured with GAS at once time. 68.5% of the people gave positive attitude toward older people. Knowledge was measured with FAQ scale at once time. 51.1% of the participants have maximum knowledge about older people. Interpretation of chi square showed there was no correlation between attitude and knowledge of the physical therapy clinicians (p > 0.05). Conclusion: This study concluded that clinical physical therapists were bearing positive attitude towards older people being aware of the ageism facts. However, there was no correlation found between clinician’s knowledge and ageism attitude